A critical examination of the usefulness of taxonomies for comparing cognitive functions across sports - Will, L.; Musculus, L.; Zentgraf, K.; De Haan, H.; Redlich, D.; Raab, M. (European Journal of Sport Science, 2026)
ABSTRACT Taxonomies are widely used in sport science to classify disciplines according to structural, cognitive, and physiological demands, yet their robustness in differentiating athletes' cognitive performance remains uncertain. This study examined whether commonly applied sport classification frameworks - open versus closed skills, strategic-static-interceptive, participant classification, and multidimensional team/precision-skill/speed-strength - meaningfully represent cognitive differences within junior and senior national squad athletes. A total of 595 national squad athletes from eight sports (artistic gymnastics, rhythmic gymnastics, trampoline, basketball, volleyball, ice hockey, table tennis, modern pentathlon) completed standardized measures of basic (processing speed, attention) and higher (working memory, inhibition, cognitive flexibility) cognitive functions. Using a model comparison approach, we show that the usefulness of taxonomic contrasts is limited because taxonomy-based models did not improve model fit relative to the null model or the model containing single sport disciplines. For processing speed, single disciplines provided the best fit. Supplementary analyses showed that processing-speed-based norm scores were above population means and moderately related to attention, but only weakly related to working memory and unrelated to executive control measures. Together, these findings suggest that conclusions about cognitive differences among high-performance athletes cannot be reliably made using taxonomic classifications as they lack robustness under realistic sampling conditions. The results underscore the importance of sport-specific and individual-level approaches when investigating cognitive functioning in high-performance sport contexts.